Insulin Resistance Indices and Carotid Intima-media Thickness in Physically Fit Adults: CHIEF Atherosclerosis Study - Lin, Yen-Po; Hsu, Yi-Chiung; Tsai, Kun-Zhe; Kwon, Younghoon; Lin, Gen-Min (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Aims: This study aims to examine the associations between various non-insulin-based insulin resistance (nIIR) indices and subclinical atherosclerosis assessed by carotid intima-media thickness (cIMT) in young adults. Background: nIIR indices, e.g., serum triglycerides (TG) have been reported with an association with cIMT in middle- and old-aged adults. Objective: We examined the associations of various well-known nIIR indices reported before with cIMT in young adults. Methods: A total of 1,822 young adults free of diabetes in Taiwan were included in 2018-2020. nIIR indices were assessed by TG concentrations, the TyG index, defined as Ln (TG *fasting glucose/2), the TG/high-density lipoprotein cholesterol (HDL-C) ratio, defined as TG divided by HDL-C, and the metabolic score for IR (METS-IR), defined as Ln[(2*fasting glucose)+TG) * body mass index (BMI)/(Ln(HDL-C))]. Multivariable linear regression analyses with adjustments for age, sex, anthropometrics, smoking, alcohol consumption, blood pressure, and total cholesterol were used to determine the associations. For TG only, HDL-C and fasting glucose were additionally adjusted. Results: In the overall participants, there was an association between cIMT and TG (β: 0.057, p = 0.04). In subgroup analyses, cIMT was associated with TG (β: 0.127, p = 0.004), the TyG index (β: 0.119, p = 0.01), and TG/HDL-C (β: 0.081, p = 0.03) in the overweight / obese (BMI ≥25 kg/m2), while not in the normal weight individuals. However, cIMT was correlated with TG (β: 0.086, p = 0.01) and TG/HDL-C (β: 0.077, p = 0.01) in those without hyperuricemia, while not in those with hyperuricemia. No association between the METS-IR and cIMT in any young adult subgroups was observed. Conclusion: This study highlights that some nIIR indices could be used to assess cIMT in young adults, particularly for those with obesity and those without hyperuricemia. The TG-based indices instead of the novel marker, METS-IR, are suggestive as stronger predictors of greater cIMT in young adults.
Keywords: TyG index